Humanitarian Diplomacy: Indonesia’s Response Toward Rohingya Humanitarian Crisis - Inda Mustika Permata; Nadya Hijrah D; Anita A Sinulingga (Journal of Diplomacy and International Studies, 2019)
This paper seeks to explain Indonesia's response to the Rohingya humanitarian crisis in Myanmar in 2017. The purpose of this paper is to explain Indonesia's success in opening up humanitarian space. The Rohingya humanitarian crisis has come to international attention with manifestations such as the pressure on the Myanmar government to stabilize its domestic security, calls for dialogue, and the provision of humanitarian assistance by the United Nations. However, Myanmar declined the invitation and withheld the assistance provided. Amid the refusal, Indonesia emerged as an actor who sought to help deal with the humanitarian crisis which was responded positively by Myanmar. Indonesia's response to the crisis in 2017 was different when the crisis that occurred in 2012, i.e Indonesia rise the Rohingya crisis as a joint problem in the OIC and ASEAN forums. This paper uses qualitative methods using secondary data. The conceptual framework used is humanitarian diplomacy. The findings of this paper are that Indonesia responded to the crisis by coordinating with Bangladesh after holding a dialogue with the Myanmar government to open up humanitarian space. Furthermore, the establishment of AKIM shows that the response of the Indonesian government was also encouraged by Islamic groups in Indonesia. Indonesia's success is due to Indonesia's good track record of Myanmar.